Analysis of Total Phenolic Content and Antibacterial Activity of Black Pomegranate Peel (Punica granatum L.) as an Antibiotic Agent Innovation - Allinha Yusfin Innaya; Majida Ramadhan; Syauqi, Ahmad (The Journal of Pure and Applied Chemistry Research, 2025)
Pomegranate is one of the most potential natural resources due to its various compounds, especially in black pomegranate skin. Pomegranate peels are often considered as unusable residue. However, black pomegranate peels have high potential phenolic content and antibacterial properties than other types of pomegranates. This study aims to analyze the total phenolic content and test the antibacterial activity of black pomegranate peel as an antibiotic agent. The method used on the total phenolic content is Folin-Ciocalteau method with UV-VIS Spectrophotometer. Meanwhile, the antibacterial activity test was carried out by the diffusion method with MHA and MHB media against Gram-Positive and Gram-Negative bacteria, namely Eschericia coli and Staphylococcus aureus and positive control using apmhicilin and chloramphenicol. Bacteria were streaked on sterile solid media using sterile cotton buds. The results obtained on the total phenolic content of black pomegranate skin resulted in 90.89 μg GAE/mL sample. Meanwhile, the antibacterial properties obtained the largest diameter of the inhibition zone on Eschericia coli and Staphylococcus aureus respectively, namely 23.4 ± 0.19 and 21.7 ± 0.35 mm. The results showed that black pomegranate peel contributes significantly to environmentally friendly antibacterial properties and can be an innovation in antibiotic development. These findings, open up new opportunities in the formulation of natural antibiotic products that are effective and safe for humans.